Solitary extranodal Rosai-Dorfman disease of the mandible: an exceedingly rare presentation - Ameer Hamza; Zhifei Zhang; Basim Al-Khafaji (University of São Paulo, 2018)
Sinus histiocytosis with massive lymphadenopathy, generally known by the name of Rosai-Dorfman disease is a rare benign condition principally affecting cervical lymph nodes. Concurrent extra-nodal disease frequently occurs, however, solitary extra-nodal disease involving the mandible is exceedingly rare with less than five reported cases in the English literature. We describe a case of primary involvement of the mandible in a 27-year-old female, and discuss the differential diagnosis of this disease with other histiocytic lesions.